2015
DOI: 10.1016/j.bbadis.2014.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Treatment in vitro with PPARα and PPARγ ligands drives M1-to-M2 polarization of macrophages from T. cruzi-infected mice

Abstract: Trypanosoma cruzi, the etiological agent of Chagas' disease, induces a persistent inflammatory response. Macrophages are a first line cell phenotype involved in the clearance of infection. Upon parasite uptake, these cells increase inflammatory mediators like NO, TNF-α, IL-1β and IL-6, leading to parasite killing. Although desired, inflammatory response perpetuation and exacerbation may lead to tissue damage. Peroxisome proliferator-activated receptors (PPARs) are ligand-dependent nuclear transcription factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 42 publications
5
85
1
Order By: Relevance
“…Apo F activated PPARγ in male neutrophils (Fig. 7h), consistent with inhibition of IL6 and induction of Ym1 and CD206 [46, 64, 65]. This effect was attenuated by CD36i.…”
Section: Resultssupporting
confidence: 69%
“…Apo F activated PPARγ in male neutrophils (Fig. 7h), consistent with inhibition of IL6 and induction of Ym1 and CD206 [46, 64, 65]. This effect was attenuated by CD36i.…”
Section: Resultssupporting
confidence: 69%
“…20,4951 After S-GO or L-GO treatment in J774.A1 cells for 24 h, no significant induction of Arg1 + cells was demonstrated compared to untreated cells (Figure 5A, P > 0.05). In contrast, induction of iNOS + cells was significantly increased in GO-treated cells, with a 21-fold increase for S-GO-treated cells and a 31-fold increase for L-GO-treated cells, compared to untreated cells (Figure 5B, P < 0.001).…”
Section: Resultsmentioning
confidence: 93%
“…A selective inhibitor for soluble TNF receptors was beneficial for the treatment of mycobacterial infections through neutralization of excessive TNF (49). Extensive studies have reported the roles of PPAR-a agonists in the modulation of innate and adaptive immune responses (50)(51)(52). These data thus indicate that PPAR-a agonists may protect hosts against excessive inflammatory responses during mycobacterial infection to promote a balanced inflammatory response.…”
Section: Discussionmentioning
confidence: 99%